Jeanne E. Arnold, Anthony P. Graesch, Enzo Ragazzini, Elinor Ochs: Life at Home in the Twenty-First Century – 32 Families Open their Doors - Dalby, Andrew (Petits Propos Culinaires, 2013)
Jeanne E. Arnold, Anthony P. Graesch, Enzo Ragazzini, Elinor Ochs: Life at Home in the Twenty-First Century – 32 Families Open their Doors: Cotsen Institute of Archaeology Press, UCLA, 2012: 172 pp., colour photography, hardback, £22.50.